Field-Effect Transistor Based on 2D Microcrystalline MoS2 Film Grown by Sulfurization of Atomically Layer Deposited MoO3 - Ivan V. Zabrosaev; Maxim G. Kozodaev; Roman I. Romanov; Anna G. Chernikova; Prabhash Mishra; Natalia V. Doroshina; Aleksey V. Arsenin; Valentyn S. Volkov; Alexandra A. Koroleva; Andrey M. Markeev (Nanomaterials, 2022)
Atomically thin molybdenum disulfide (MoS2) is a promising channel material for next-generation thin-body field-effect transistors (FETs), which makes the development of methods allowing for its controllable synthesis over a large area an essential task. Currently, one of the cost-effective ways of its synthesis is the sulfurization of preliminary grown oxide- or metallic film. However, despite apparent progress in this field, the electronic quality of the obtained MoS2 is inferior to that of exfoliated samples, making the detailed investigation of the sulfurized films’ properties of great interest. In this work, we synthesized continuous MoS2 films with a thickness of ≈2.2 nm via the sulfurization of an atomic-layer-deposited MoO3 layer. X-ray photoelectron spectroscopy, transmission electron microscopy, and Raman spectroscopy indicated the appropriate chemical composition and microcrystalline structure of the obtained MoS2 films. The semiconductor quality of the synthesized films was confirmed by the fabrication of a field-effect transistor (FET) with an Ion/Ioff ratio of ≈40, which was limited primarily by the high contact resistance. The Schottky barrier height at the Au/MoS2 interface was found to be ≈1.2 eV indicating the necessity of careful contact engineering. Due to its simplicity and cost-effectiveness, such a technique of MoS2 synthesis still appears to be highly attractive for its applications in next-generation microelectronics. Therefore, further research of the electronic properties of films obtained via this technique is required.